Differentiation of Stem Cells From Human Exfoliated Deciduous Teeth Toward a Phenotype of Corneal Epithelium In Vitro. Issue 11 (November 2015) - Unknown
Abstract : Purpose: The aim of this study was to characterize stem cells from human exfoliated deciduous teeth (SHED) and to investigate the potential of SHED to differentiate toward corneal epithelium-like cells in vitro. Methods: Mesenchymal and embryonic stem cell markers were analyzed by flow cytometry. The SHED was cocultured in either a transwell noncontact system or in a mixed culture system with immortalized human corneal epithelial (HCE-T) cells to induce the epithelial transdifferentiation. Expression of the mature corneal epithelium–specific marker cytokeratin 3 (CK3) and corneal epithelial progenitor marker cytokeratin 19 (CK19) were detected by immunofluorescence and the reverse transcription–polymerase chain reaction, respectively. Results: SHED strongly expressed a set of mesenchymal stromal cell markers and pluripotency markers including NANOG and OCT-4. Seven days after the transwells were cocultured with HCE-T cells, SHED successfully upregulated epithelial lineage markers CK3 (16.6 ± 7.9%) and CK19 (10.0 ± 4.3%) demonstrating the potential for epithelial transdifferentiation, whereas CK3 and CK19 were barely expressed in SHED when cultured alone. Expression of transcript levels of CK3 and CK19 were significantly upregulated when SHED were transwell cocultured or mixed cultured with HCE-T cells by 7, 14, and 21 days. Conclusions: We have demonstrated that SHED retain the potential for transdifferentiation to corneal epithelium-like cells by in vitro coculture with immortal corneal epithelium cells. Thus, exfoliated teeth may be an alternative tissue resource for providing stem cells for potential clinical applications in ocular surface regeneration.